PENGARUH PEMBERIAN PUPUK CAIR RUMPUT LAUT TERHADAP PERTUMBUHAN PEMBIBITAN KELAPA SAWIT (Elaeis guineensis Jacq) DI PRE NURSERY - Eka Bobby Febrianto; Sri Murti Tarigan; Apridho Efraim (Universitas Asahan, 2022)
The Effect of Seaweed Liquid Fertilizer on the Growth of Oil Palm (Elaeis guineensis Jacq) in Pre Nursery. The purpose of this research is. Knowing the growth response of oil palm seedlings (Elaeis guineensis Jacq) with the application of liquid seaweed fertilizer. This research was conducted from July 2020 - September 2020, starting from sampling the height of the seeds, the number of leaves, the diameter of the stem, the wet weight of the plant, the dry weight of the plant to data processing. This study used a non-factorial randomized block design (RBD) method, namely by collecting samples of seed height, number of leaves, stem diameter, plant wet weight, plant dry weight to be analyzed by Analysis of Variance (ANOVA) with the continued test of Duncan's Multiple Range Test. (DMRT) at the 5% level. Key words: Oil palm, Pre Nursery, Seaweed